Rethinking the Constitutionality of Indonesia’s Flawed Anti-Blasphemy Law - Cekli Setya Pratiwi (Constitutional Review, 2021)
This study examines the constitutionality of Indonesia’s Anti-Blasphemy Law, which has been challenged unsuccessfully at the Constitutional Court on three occasions, in 2009, 2012, and 2018. While the Court has acknowledged the law’s provisions are open to multiple interpretations, it insists on maintaining the law as it is, on the grounds that the right to religious expression is not absolute, as freedom and rights are restricted under Article 28J of the 1945 Constitution. The Court believes that canceling the law would create a dangerous legal vacuum. The ambiguity of the Court’s decisions on the constitutionality of the Anti-Blasphemy Law is illustrated in recent blasphemy cases that have not been explored in previous studies. This study uses a doctrinal legal approach to examine why the Anti-Blasphemy Law is flawed and to analyze to what extent the ‘particular constitutionalism’ approach influenced the Court’s decisions when declaring the constitutionality of the law. As such, the Court’s misinterpretation of the core principles of the competing rights – the right to religious freedom and the right to freedom of expression – and its standard limitation, have been ignored. The findings of this study show that in dealing with the Anti-Blasphemy Law, the Court has a narrow and limited recognition of human rights law. The Court’s fear of revoking the Anti-Blasphemy Law is based only on assumptions and is less supported by facts. The Court has failed to realize that the implementation of the flawed Anti-Blasphemy Law in various cases has triggered public disorder, with people taking justice into their own hands.